Effect of Instructional Strategies and Spatial Intelligence on Learning Outcomes of Mathematics - Nuke Lu'Lu Ul Chusna S , Zulfiati Syahrial , Nurdin Ibrahim , Jarudin (International Journal of Advanced Science and Technology, 2020)
This study aims to obtain a picture of the influence of Inquiry instructional Strategies andConventional instructional Strategies, which are external factors and students' high and lowSpatial Intelligence. The sample used in this study was taken by simple random sampling, namelyby drawing lots, if the first number comes out as an experimental class and the second numbercomes out then it becomes the control class. In the drawing process, the experimental class isclass A and the control class is class B. Before each class is treated, students will be given aspatial intelligence test and a discrete mathematical test, in order to obtain a spatial intelligencescore and the results of the initial discrete mathematics assessment. Furthermore, the scoresobtained by students for spatial intelligence are sorted from the lowest score to the highest score,for the grouping of students based on high and low spatial intelligence. The value of changes inmath learning outcomes without the need to be influenced by the existence of instructionalstrategies and special intelligence, meaning that without the influence of independent variables,the dependent variable can change in value, if Significance (Sig.) <0.05 (α). Based on the resultsof the hypothesis test above that instructional strategy and spacial Intelligence significantlyinfluence the learning outcomes of science that are significant 0.000 <0.05 (α) it can beconcluded that influence between instructional strategies and special intelligence on mathlearning outcomes. The results of the study that instructional strategies and spatial intelligencehave a significant effect on learning outcomes in mathematics